Reflections on the validity of exculpatory clauses in light of Section 6:152 of the Hungarian Civil Code - Pusztahelyi, Réka (Pro Futuro, 2020)
A magyar Ptk. 6:152. szakasza a felelősségkizáró és korlátozó kikötések érvénytelenségének általános, a szerződési szabadság határát kijelölő abszolút jellegű minimumszabálya. Jelen tanulmányban e szabály összetett vizsgálatára törekszünk. Szükséges ugyanis a károkozás jogellenességét kizáró károsulti beleegyezés, a kockázat tudatos vállalása illetve a joglemondás (itt elsősorban a szerződésszegésből fakadó igények érvényesítéséről való lemondás) mint jognyilatkozat elemzése is. Ugyanígy vizsgáljuk e tilalom más érvénytelenségi okokkal való viszonyát, elsősorban a tisztességtelen általános szerződési feltételek tényállását. Section 6:152 of the Hungarian Civil Code (HCC) is an objective cap on the freedom of contract, it is an unconditional (absolute) and minimum protection to which all exculpatory clauses are subject. In this essay, this rule is examined in a wide and complex context. These exculpatory clauses are closely connected to the consent of an injured person or their assumption of risk, or their waiver (especially waiving claims for damages) as unilateral juridical acts. The relationship between this statute and other grounds of invalidity shall also be examined, especially the connection to the invalidity rule of unfair standard contract terms.